Synthesis and Biological Evaluation of New Triazolo‐ and Imidazolopyridine RORγt Inverse Agonists. (30th November 2016) - Hintermann, Samuel; Guntermann, Christine; Mattes, Henri; Carcache, David A.; Wagner, Juergen; Vulpetti, Anna; Billich, Andreas; Dawson, Janet; Kaupmann, Klemens; Kallen, Joerg; Stringer, Rowan; Orain, David
Abstract: Retinoic‐acid‐related orphan receptor γt (RORγt) is a key transcription factor implicated in the production of pro‐inflammatory Th17 cytokines, which drive a number of autoimmune diseases. Despite diverse chemical series having been reported, combining high potency with a good physicochemical profile has been a very challenging task in the RORγt inhibitor field. Based on available chemical structures and incorporating in‐house knowledge, a new series of triazolo‐ and imidazopyridine RORγt inverse agonists was designed. In addition, replacement of the terminal cyclopentylamide metabolic soft spot by five‐membered heterocycles was investigated. From our efforts, we identified an optimal 6, 7, 8‐substituted imidazo[1, 2‐ a ]pyridine core system and a 5‐ tert ‐butyl‐1, 2, 4‐oxadiazole as cyclopentylamide replacement leading to compounds10 (( S )‐ N ‐(8‐((4‐(cyclopentanecarbonyl)‐3‐methylpiperazin‐1‐yl)methyl)‐7‐methylimidazo[1, 2‐ a ]pyridin‐6‐yl)‐2‐methylpyrimidine‐5‐carboxamide) and33 (( S )‐ N ‐(8‐((4‐(5‐( tert ‐butyl)‐1, 2, 4‐oxadiazol‐3‐yl)‐3‐methylpiperazin‐1‐yl)methyl)‐7‐methylimidazo[1, 2‐ a ]pyridin‐6‐yl)‐2‐methylpyrimidine‐5‐carboxamide). Both derivatives showed good pharmacological potencies in biochemical and cell‐based assays combined with excellent physicochemical properties, including low to medium plasma protein binding across species. Finally, 10 and33 were shown to be active in a rodent pharmacokinetic/pharmacodynamic (PK/PD) model after oral gavage at 15 mg kg −1, lowering IL‐17 cytokine production in ex vivo antigen recall assays. Abstract : Autoimmune challenge : A new series of RORγt inverse agonists containing triazolo‐ and imidazopyridine cores has been identified. Compounds based on the 6, 7, 8‐substituted imidazo[1, 2‐ a ]pyridine core retained high potencies on the target plus an advantageous physicochemical profile including medium to high free fraction across species. Derivatives10 and33 showed in vivo efficacy in a rat PK/PD model and inhibited IL‐17A production in an ex vivo challenge.